Resiliensi Perawat Puskesmas dalam Menghadapi Kondisi Pandemi COVID-19 - Sari, Yuyun Kartika; Somantri, Irman; Yulianita, Henny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to identify Puskesmas nurses' resilience in facing the COVID-19 pandemic in Bandung City. The method used is quantitative descriptive. The research results showed that the majority of Bandung City Health Center nurses had moderate resilience (41.2%), others had low stability (35.3%), and a small number had high strength (23.5%). The aspect of resilience with the highest average is spiritual influence, and the lowest is trusting one's instincts, tolerance for negative things, and the strength to deal with stress. In conclusion, in facing the COVID-19 pandemic, most Bandung City Community Health Center nurses have good resilience. Keywords: COVID-19, Nurse, Community Health Center, Resilience